2007
DOI: 10.1093/ecam/nem016
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulating Activity of Agaricus brasiliensis KA21 in Mice and in Human Volunteers

Abstract: We performed studies on murine models and human volunteers to examine the immunoenhancing effects of the naturally outdoor-cultivated fruit body of Agaricus brasiliensis KA21 (i.e. Agaricus blazei). Antitumor, leukocyte-enhancing, hepatopathy-alleviating and endotoxin shock-alleviating effects were found in mice. In the human study, percentage body fat, percentage visceral fat, blood cholesterol level and blood glucose level were decreased, and natural killer cell activity was increased. Taken together, the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 58 publications
1
37
0
2
Order By: Relevance
“…These data suggest a dose-dependent hipoglycemic activity of that mushroom. The Agaricus brasiliensis has been commonly used in the treatment of many diseases, including diabetes [34] and the present results suggest that there is a support for this health claim. Others studies with diabetics animals are necessary to verify an possible hypoglycemic effect of the A. brasiliensis mycelium.…”
Section: Discussionsupporting
confidence: 65%
“…These data suggest a dose-dependent hipoglycemic activity of that mushroom. The Agaricus brasiliensis has been commonly used in the treatment of many diseases, including diabetes [34] and the present results suggest that there is a support for this health claim. Others studies with diabetics animals are necessary to verify an possible hypoglycemic effect of the A. brasiliensis mycelium.…”
Section: Discussionsupporting
confidence: 65%
“…Antifungal properties (Bernardshaw et al, 2005), antivirals (Sorimachi et al, 2001), antioxidant properties (Oliveira et al, 2007;Soares et al, 2009) and antiallergic properties (Ellertsen and Hetland, 2009;Mizuno, 2010). In addition, it lowers blood cholesterol, stimulates the immune system, and is effective for treating AIDS (Mizuno, 2010;Liu et al, 2008;Lima et al, 2011). Watanabe et al (2002), Kim et al (2005) and Liu et al (2008) have shown that mushroom extract can also be used to treat diabetes, hypertension and viral hepatitis.…”
Section: Biological Materialsmentioning
confidence: 99%
“…In addition, it lowers blood cholesterol, stimulates the immune system, and is effective for treating AIDS (Mizuno, 2010;Liu et al, 2008;Lima et al, 2011). Watanabe et al (2002), Kim et al (2005) and Liu et al (2008) have shown that mushroom extract can also be used to treat diabetes, hypertension and viral hepatitis.…”
Section: Biological Materialsmentioning
confidence: 99%
“…Particularly, AgCAS strongly induced IFN-γ secretion from GM-CSF-treated murine splenocytes. This observation suggested that this fraction may contribute to the NK activation caused by the intake of A. brasiliensis fruiting body, given that IFN-γ is a mediator of NK activity [7,8]. Furthermore, given that GM-CSF is now considered the most important factor for up-regulating the reactivity of immune cells to 1,3-β-glucan [28,29], we hypothesized that cytokine synthesis induced by the Agaricus extracts may be due to their 1,3-β-glucan content.…”
Section: Discussionmentioning
confidence: 95%
“…(A. brasiliensis) is a traditional medicinal mushroom used worldwide as a biological response modifier (BRM) [1][2][3], because its β-glucan-rich fruiting body exhibits potent immunoenhancing activity [4][5][6]. For instance, our previous clinical study revealed that natural killer (NK)-cell activity was up-regulated after intake of the A. brasiliensis fruiting body without any adverse effects [7]. In addition, it has been reported that the A. brasiliensis-induced augmentation of NK activity is principally mediated by interferon-γ (IFN-γ) [8].…”
Section: Introductionmentioning
confidence: 99%